Analisis Efektivitas Studi Independen (MBKM) Pada Mahasiswa Teknik Informatika Menggunakan Algoritma K-Nearest Neighbor - Faqihuddin Hanif, Isa; Apoko, Tri Wintolo; Hendriana, Benny; Handayani, Isnaini; Fatayan, Arum; Irdalisa, Irdalisa (Building of Informatics, Technology and Science (BITS), 2024)
The Merdeka Study Program is part of the Kampus Merdeka (MBKM) policy initiated by the Minister of Education and Culture, Nadiem Makarim. Students are given the opportunity to expand their knowledge and skills, both hard and soft, through various off-campus activities. In the Informatics Engineering Study Program at UHAMKA, this program is designed to enrich learning experiences and enhance practical skills relevant to the industry. The program's effectiveness evaluation is conducted through a survey of 41 students to collect data on their experiences and perceptions. The aim is to measure the extent to which the MBKM program positively impacts student learning. The research methodology uses the K-Nearest Neighbor (KNN) algorithm to classify program effectiveness data based on several performance indicators. The analyzed data includes survey results from students who participated in the MBKM program. The research findings show that the KNN classification model has an accuracy of 93.65%, with an average precision of 94.08% and recall of 93.65%, indicating a high level of accuracy in classifying program effectiveness. Most students reported that the MBKM program is very effective in enhancing their skills and knowledge, although some felt neutral or found it less effective. This study concludes that the MBKM program is generally effective in achieving its goals, although improvements and adjustments are still needed to optimize its benefits for all students